Risk factors and timing of suicide attempts among US Army Reserve Component soldiers during deployment to the Afghanistan and Iraq wars: Results from the Army Study to Assess Risk and Resilience in Servicemembers - Stokes, Cara M. (Psychiatry, 2019)
OBJECTIVE: During the wars in Afghanistan and Iraq, suicidal behaviors increased among U.S. Army soldiers. Although Reserve Component (RC) soldiers (National Guard and Army Reserve) comprise approximately one third of those deployed in support of the wars, few studies have examined suicidal behaviors among these “citizen-soldiers”. The objective of this study is to examine suicide attempt risk factors and timing among RC enlisted soldiers. METHODS: This longitudinal, retrospective cohort study used individual-level person-month records from Army and Department of Defense administrative data systems to examine socio-demographic, service-related, and mental health predictors of medically documented suicide attempts among enlisted RC soldiers during deployment from 2004–2009. Data were analyzed using discrete-time survival models. RESULTS: A total of 230 enlisted RC soldiers attempted suicide. Overall, the in-theater suicide attempt rate among RC soldiers was 81/100,000 person-years. Risk was highest in the fifth month of deployment (13.76 per 100,000 person-months). Suicide attempts were more likely among soldiers who were women (adjusted odds ratio, aOR=2.5 [95% CI: 1.8–3.5]), less than high school educated (aOR=1.8 [95% CI: 1.3–2.5]), in their first two years of service (aOR=2.0 [95% CI: 1.2–3.4]), were currently married (aOR=2.0 [95% CI: 1.5–2.7], and had received a mental health diagnosis in the previous month (aOR= 24.7 [95% CI: 17.4–35.0]). CONCLUSIONS: Being female, early in service and currently married are associated with increased odds of suicide attempt in RC soldiers. Risk of suicide attempt was greatest at mid deployment. These predictors and the timing of suicide attempt for RC soldiers in-theater is largely consistent with those of deployed Active Component (Regular) soldiers. Results also reinforce and replicate the findings among Active Component soldiers related to the importance of a recent mental health diagnosis and the mid-deployment as a period of enhanced risk.